Brønsted Acid Catalyzed Carbocyclizations Involving Electrophilic Activation of Alkynes - Hermange, Philippe; Gicquiaud, Julien; Barbier, Morgan; Karnat, Alexandre; Toullec, Patrick Y. (Synthesis, 2022)
This review focuses on the carbocyclization reactions of alkyne-containing substrates catalyzed by Brønsted acids. The electrophilic activation occurs either by direct protonation of the alkyne or by formation of an intermediate cation that further reacts with the alkyne to give a key vinyl cation intermediate. Specific focus is placed on the selectivity of the various methodologies described herein and on mechanistic rationales.1 Introduction2 Brønsted Acid Catalyzed Alkyne Carbocyclization Involving C(sp) Reaction Partners2.1 Brønsted Acid Catalyzed Cyclization of Diynes2.2 Brønsted Acid Catalyzed Cyclization of Allenynes3 Brønsted Acid Catalyzed Alkyne Carbocyclization Involving C(sp2) Reaction Partners3.1 Brønsted Acid Catalyzed Cycloisomerization of Enynes3.1.1 Initial Protonation of the Alkene Function3.1.2 Initial Protonation of the Alkyne Function3.1.3 A Conia-Ene Reaction3.2 Electrophile-Induced Carbocyclization Involving Other C(sp2)-Based Reaction Partners3.2.1 Iminium Electrophiles3.2.2 Oxonium Electrophiles3.2.3 Isocyanate and Thioisocyanate Electrophiles3.3 Brønsted Acid Catalyzed Cycloisomerization of Aryl-alkynes3.3.1 Reactions Using Excess or Stoichiometric Amounts of Brønsted Acid3.3.2 Reactions Using Substoichiometric Amounts of Brønsted Acid3.3.3 Heteroatom-Substituted Alkynes3.3.4 Enantioselective Brønsted Acid Catalyzed Cycloisomerization of Aryl-alkynes4 Brønsted Acid Catalyzed Alkyne Carbocyclization Involving C(sp3) Reaction Partners: Alkyne-alkane Cycloisomerization5 Conclusion and Outlook
Keywords: carbocyclization; alkynes; vinyl cation; Brønsted acid